2017
DOI: 10.21037/jss.2017.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive endoscopic spinal cord untethering: case report

Abstract: Tethered cord syndrome is a constellation of symptoms and signs that include back and leg pain, bowel and bladder dysfunction, scoliosis and lower extremity weakness and deformity. Tethering may be due to a tight filum terminale or a form of spinal dysraphism. The authors present a case of a 40-year-old man who presented with symptoms of back pain, bilateral lower extremity radicular pain, and bowel and bladder dysfunction. Magnetic resonance imaging showed a sacral lipomyelomeningocele, with fat tracking supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In the study of Potts et al, an average of 300 ml of bleeding was observed with open surgery (7). Significant blood loss and postoperative scarring are also associated with the muscle dissection in this approach (7,11). In our study, patients average blood loss was 30 ml.…”
Section: █ Discussionsupporting
confidence: 48%
“…In the study of Potts et al, an average of 300 ml of bleeding was observed with open surgery (7). Significant blood loss and postoperative scarring are also associated with the muscle dissection in this approach (7,11). In our study, patients average blood loss was 30 ml.…”
Section: █ Discussionsupporting
confidence: 48%
“…In this video article, we will examine a case of tethered cord release using a minimally invasive spinal surgery technique called biportal endoscopic approach, 1 which has become increasingly popular in recent years. [2][3][4][5][6][7][8][9] 0:34 Case Presentation. Our patient is a 24-year-old female who has been experiencing severe back pain radiating to the buttocks with episodic attacks for the past 8 years.…”
Section: Transcriptmentioning
confidence: 99%
“…As endoscopic spine surgery continues to enjoy wider adoption, spine surgeons are expanding potential indications for use of this technology. Numerous case series have shown potential applications in patients with complex pathology including burst fractures (113), BMP related heterotopic ossification (114,115), synovial cysts (116,117), migrated hardware (115), discitis (118), spinal cord untethering (119), and tumors (120) (Figure 8). While direct comparisons to more traditional techniques for these complex scenarios is limited, current available evidence highlights the versatility of endoscopic spine surgery in achieving favorable outcome with minimal morbidity.…”
Section: Revision Surgery and Previous Arthrodesismentioning
confidence: 99%